FSMP-02. CHANGES IN GLUTAMINE METABOLISM INDUCED BY OXALOACETATE IN GLIOBLASTOMA. (25th March 2021) - Ijare, Omkar; Conway, David; Cash, Alan; Baskin, David; Pichumani, Kumar
Abstract: Anhydrous Enol-Oxaloacetate (AEO) has been shown to significantly increase survival and decrease tumor growth rates in animal models of glioblastoma and hepatocellular carcinoma. In the body, AEO is metabolized to "oxaloacetate" (OAA). Earlier, we demonstrated that AEO drastically reduced Warburg glycolysis in glioblastoma cells which was determined by the increase in pyruvate to lactate ratio and a 48.8% decrease in lactate production in 13 C-labeled glucose metabolism studies. We have expanded this previous work to examine 13 C-labeled glutamine metabolism. Cultured solid tumor cancer cells strongly rely on both glucose and glutamine to synthesize carbon intermediates for anaplerotic reactions. With treatment of OAA, we hypothesize that glutamine-derived OAA may be reduced which can be tracked through the use GC-MS based 13 C-labeled glutamine isotopomer experiments. Patient-derived glioblastoma cells were grown in 15 mM glucose and 2 mM glutamine containing DMEM medium supplemented with 2 mM OAA for 10 days. 24 hours prior to harvesting the cells, 4 mM of [U- 13 C]glutamine was introduced to the medium. OAA treated cells showed significant decrease in the protein levels of lactate dehydrogenase A and C which indicates the switching off of glycolysis to support the utilization of elevated OAA levels during glutamine metabolism in the TCA cycle. 13 C mass distribution analysis showed significant decrease in malate, aspartate and citrate pools (malate: 8.8%, p = 0.0098; aspartate: 9.2%, p = 0.0064; citrate: 9.5%, p = 0.0036) in their M+4 isotopomer labeling in OAA treated group compared to the control group. Decrease in lactate generation may reduce cancer proliferation, migration and invasion. Together, these data provide alternative way to modulate energy metabolism in glioblastoma using AEO treatment. Similarly, AEO treatment in other solid tumors (e.g. pancreatic ductal adenocarcinoma) may produce altered glutamine metabolism which may be of therapeutic value.